Effect of lysine acetylation on the regulation of Trypanosoma brucei glycosomal aldolase activity - Leite, Ariely Barbosa; Gomes, Antoniel Augusto Severo [UNESP]; Sousa, Ana Caroline De Castro Nascimento; Fontes, Marcos Roberto De Mattos [UNESP]; Schenkman, Sergio; Moretti, Nilmar Silvio (Portland Press, 2020)
Post-translational modifications provide suitable mechanisms for cellular adaptation to environmental changes. Lysine acetylation is one of these modifications and occurs with the addition of an acetyl group to Nϵ-amino chain of this residue, eliminating its positive charge. Recently, we found distinct acetylation profiles of procyclic and bloodstream forms of Trypanosoma brucei, the agent of African Trypanosomiasis. Interestingly, glycolytic enzymes were more acetylated in the procyclic, which develops in insects and uses oxidative phosphorylation to obtain energy, compared with the bloodstream form, whose main source of energy is glycolysis. Here, we investigated whether acetylation regulates the T. brucei fructose 1,6-bisphosphate aldolase. We found that aldolase activity was reduced in procyclic parasites cultivated in the absence of glucose and partial recovered by in vitro deacetylation. Similarly, acetylation of protein extracts from procyclics cultivated in glucose-rich medium, caused a reduction in the aldolase activity. In addition, aldolase acetylation levels were higher in procyclics cultivated in the absence of glucose compared with those cultivated in the presence of glucose. To further confirm the role of acetylation, lysine residues near the catalytic site were substituted by glutamine in recombinant T. brucei aldolase. These replacements, especially K157, inhibited enzymatic activity, changed the electrostatic surface potential, decrease substrate binding and modify the catalytic pocket structure of the enzyme, as predicted by in silico analysis. Taken together, these data confirm the role of acetylation in regulating the activity of an enzyme from the glycolytic pathway of T. brucei, expanding the factors responsible for regulating important pathways in this parasite.